Utterances in The 2017 Jakarta Gubernatorial Debate of Regional Election - Dewi Nuryanti (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2019)
The purpose of this study was to describe the functions of various utterances uttered by the candidates during the debate for the Jakarta Gubernatorial election. The study utilized a descriptive qualitative research approach, specifically focusing on describing spoken utterances. The theoretical framework applied was the theory of speech acts by Austin and Searle. Data were sourced from the Jakarta Gubernatorial debate during the regional election and downloaded from https://www.youtube.com/. The analysis revealed that the candidates used their utterances to inform the public about certain conditions in Jakarta using declarative utterances. They aimed to express their beliefs on various matters, hoping to influence their voters to share the same perspectives. The candidates predicted that they would transform Jakarta into a more modern and secure city, bringing prosperity within the next five years. They also expressed gratitude for favourable conditions while sometimes offering criticisms or complaints. Additionally, they highlighted positive attributes of others, showcasing mutual praise. Their utterances were intended to persuade or call upon the audience to take certain actions and commit to fighting against drug issues in Jakarta.